MEDICATION USE IN NEONATAL INTENSIVE CARE UNITS ACROSS EUROPE. Issue 1 (14th December 2015) - Mesek, Inge; Nellis, Georgi; Lass, Jana; Lutsar, Irja
Abstract : Objectives: This is the first Europe-wide study aiming to describe the medication use in Neonatal Intensive Care Units and to analyse the factors that might influence the prescription pattern. Methods: A pan-European one day point-prevalence study was conducted in 2012 where all of the prescriptions for hospitalised neonates were recorded. A trade name, manufacturer, active pharmaceutical ingredients (API), strength, galenic form and route of administration were registered. Results: Altogether 2173 prescriptions were administered to 726 neonates from 21 countries, of whom 66% (477/726) were preterm, 12% (84/726) extremely preterm. There was inverse correlation between gestational age (GA) and median number of prescriptions per neonate (group median 2/IQR 1–4, extremely preterm 4/3–6, very preterm 3/2–5, late preterm 2/1–3, full-term 2/1–3). Median number of prescriptions per neonate was highest in the eastern region, among extremely preterm neonates (median=6.5/IQR 6–8.5). Highest prescription rate was for alimentary medicines (93/per 100 admissions), systemic antiinfectives (79/100) and medicines for blood (71/100). Antiinfectives were most frequently prescribed in the southern region (103/100). Multivitamins were most frequently used medications in most regions (western 74, southern 31, northern 31/100), except in eastern region (5/100). Most commonly prescribed API-s were multivitamins (32/100), caffeine (19/100), gentamicin (18/100), amino acids (18/100) and colecalciferol (15/100). Most frequently prescribed medications among extremely preterm neonates were caffeine (60/100), among very preterms multivitamins and caffeine (45 and 43/100), among late preterms multivitamins (44/100) and among full-terms phytomenadione (26/100) and gentamicin (24/100). Conclusions: Our study revealed the most commonly used medications in neonates. Higher prescription rate among preterm neonates calls for further analysis of the suitability and safety of medications for infants with lower GA.